Relatório do estágio curricular supervisionado em medicina veterinária área de concentração: bovinocultura de corte - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The purpose of this report is to describe the activities developed during the Supervised Curricular Internship in Veterinary Medicine (ECSMV), carried out in the area of beef cattle farming, under the guidance of Prof. Dr. Tiago Gallina Corrêa. The internship was carried out at the company Sevet Consultoria Veterinária, located in the city of São Francisco de Assis - RS, under the supervision of veterinarian Rafael Gomes Severo, during the period from August 14th to November 6th, 2023, totaling 456 hours . During this period, it was possible to monitor 4,702 animals managed in nine different municipalities, operating in the clinical scope 0.4%, reproductive 66.2%, obstetric 0.6%, sanitary 32.7% and field surgeries for cattle 1 .4%. Therefore, the topic addressed for discussion was the induction of puberty in heifers and orchiectomy methods in cattle with a focus on the use of nylon cable ties to prevent hemorrhages. Therefore, ECSMV was of enormous importance for practical development, as well as improving communication with farm owners and employees.
Curricular internship report supervised in veterinary medicine area of concentration: beef cattle farming
Keywords: Orquiectomia; Abraçadeira de nylon; Cattle farming; Livestock; Indução de puberdade; Puberty induction; Orchiectomy; Nylon cable tie; Bovinocultura; Pecuária; CNPQ::CIENCIAS AGRARIAS